Penerapan Sistem Informasi Pengajuan Pensiun Pegawai Negeri Sipil di Kantor Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Aceh Barat Berbasis Web - Prayoga, M Iqbal; Maulidasari, Cut Devi (Regress: Journal of Economics & Management, 2023)
This article aims to discuss the use of information technology in carrying out its duties and functions. The role of technology is needed in various companies, seeing that every company activity cannot be carried out quickly without technology. To overcome this problem, the West Aceh Personnel and Human Resources Development Agency needs to implement a web-based information system for submitting civil service pensions. The results of the evaluation show that employees applying for retirement at the West Aceh District BKPSDM no longer need to go to BKN Banda Aceh to apply for a pension, they only need to complete the requirements requested online. This information system is made by BKN people, while BKPSDM is only a user, and this pension application is divided into two, namely Document Digital and SKPK. With the application of web-based retirement applications, it is very helpful for those in charge of Procurement, Termination and ASN Information because it makes it easier. Then it also makes it easier for employees who apply for retirement because it will speed up the retirement process so that it will produce the right information, whenever and wherever it is up to date.